Factors Related to Dropping Out in the Freshman and Sophomore Years in the Career of Teaching Mathematics at Universidad Nacional de Costa Rica - Pascua-Cantarero, Paola Michelle (2016)
This article announces outstanding details obtained through the investigation carried out, which among its objectives were to determine the factors related to student drop out during the freshman and sophomore years of higher education and bachelor’s degree in teaching mathematics (career of teaching mathematics) at National University of Costa Rica for those entering in 2007, 2008 and 2009. The mentioned research responded to a joint study, with a quantitative phase of descriptive character and a qualitative phase with a phenomenological design; its theoretical foundation was based on research on university dropout in different regions and the theory of Tinto and Spady experts regarding the causes for this problem. A database provided by the Registration Department of the National University of Costa Rica and a telephone semi-structured interviewed applied to students who defected from the major, in a final way, was used for the analysis of the information. The population in the quantitative phase was constituted by all participants who entered in the years 2007, 2008 and 2009 and dropped out in the first and second year of the career. The study group in the qualitative phase was composed by 15 informers belonging to the different cohorts 2007, 2008 and 2009 and who dropping out during the first and second year of the career. Results showed that the dropout phenomenon in the first year had similar factors as those occurred in the second year of the career of teaching mathematics. The conclusions indicate, among several factors related to dropping out in the first and second year of the 2007, 2008 and 2009 cohorts, that unmet expectations and lack of academic and social integration stand out as common factors.